Systematic Review: The use of Propolis Mouthwash in Reducing Mucositis in Cancer Patients Undergoing Chemotherapy and Radiation Therapy - Ngolu Siregar; Tuti Nuraini; Riri Maria; Yossie Susanti Eka Putri (GLOBAL HEALTH SCIENCE GROUP, 2025)
A systematic review of randomized clinical trials in cancer patients on the effectiveness of propolis mouthwash use in post-chemo and radiation cancer patients. Oral mucositis (OM) is a common and highly symptomatic complication of cancer therapy that affects function, quality of life. Chemotherapy and radiation are the most widely used interventions in cancer treatment. The prevalence of oral mucositis side effects among HNC patients is 93.9%. Research on the management of OM is still ongoing. This study aims to analyze a systematic review of the use of propolis in preventing and reducing the severity of oral mucositis in cancer patients undergoing chemo- and radiation therapy. Four databases through article searches tailored to the formulation of PICO questions consisting of ScienceDirect, Pubmed, ProQuest, Sage journals and EBSCO, A total of 2,252 articles were identified, and 8 articles were included in the final analysis. Of the ten articles selected, there were 6 articles that were suitable for oral mucositis treatment interventions that showed the effectiveness of using propolis mouthwash to treat ral mucositis with a Randomized Controlled Trial (RCT) design. The use of propolis mouthwash for oral mucositis can be done to overcome and prevent oral mucositis in cancer patients undergoing chemo and radiation therapy.